(untitled) (Journal of Misan Researches, 2021)
In the Name of Allah, the Most Beneficent, the Most Merciful “O, my Lord! so order me that I may be grateful for Thy favors, which thou hast bestowed on me and on my parents, and that I may work the righteousness that will please Thee: And admit me, by Thy Grace, to the ranks of Thy righteous Servants."Al-Ahqaf (15) To Allah Almighty has spoken the truth Praise be to Allah, Lord of the worlds, and may Allah’s prayers be upon His faithful Messenger and upon his good and pure family, from whom Allah has removed filth and purified them. Knowing money is one of the principles that why is focusing on it so important? We approached it in a simple part in the Holy Qur’an, under the title of the concept of money, as if we took it as an introduction to the topic, and through that, we entered the origin of the topic to explain its importance in the truce, which came in various narrations that did not agree on defining the victorious party in the war in order to set the appropriate conditions. One of the narrations stated that Imam Al-Hassan (PBUH) was the victor, and we showed it in its place, and this contradicted other narrations which stated that Muawiyah was the victor. In refusing to find money based on what Ibn Shabat al-Numairi reported, in what he called the charity of the Commander of the Faithful (PBUH). It is worth noting that we took the narrations from their original sources, studied them closely and in support, and commented as much as we can cognitively if we had that, and from our methodology not to write an introduction, conclusion, and a list of sources, because it is harmful to the research, our position is known about that. The order of the author of the assignment is a conclusion. This is what our time allows, and we apologize to you.